(untitled) (Revista científica Olimpia, 2016)
The sport organizations possess an important social function: to stimulate the he/she practices of the sport like a type of socially useful activity and in turn to guarantee the preparation of their human resources for the achievement of such a function. In the Club of Boxing MAS Holdings of Sri Lanka, is manifested inadequacies with relationship to the non use of the human potential that possesses, because their functions and activities are not defined you specify, to achieve satisfactory results in the sport activity and to guarantee a bigger stability in the development of the sport organization. Does the above-mentioned generate the following scientific Problem as restructuring the system management human resources of the Club of Boxing MA Holdings of Sri Lanka so bigger stability is guaranteed in the sport development? Determining as Objective: To propose the reorganization of the system management of the human resources of the Club of Boxing MAS Holdings of Sri Lanka, defining their functions and activities, so that it propitiates a bigger stability in the sport development of this specialty. For the solution of the signal situation different methods were used: Historical logical, Analysis synthesis, Inductive deductive, system Focus, theoretical Moderation, you Interview, Analysis of documents, user’s Approaches, Statistical descriptive